Factors associated with low prevalence of Fuchs' uveitis syndrome in Japan - Yoneda, Yu; Usui, Yoshihiko; Tanaka, Rie; Hase, Keitaro; Namba, Kenichi; Kamoi, Koju; Takase, Hiroshi; Takeuchi, Masaki; Matsumiya, Wataru; Kusuhara, Sentaro; Takeda, Atsunobu; Yawata, Nobuyo; et al. (Frontiers in Medicine, 2022)
Aim: To investigate the causes of low prevalence of Fuchs’ uveitis syndrome (FUS) in Japan. Methods: Medical records of 160 patients diagnosed with FUS at 14 uveitis specialty facilities in Japan were reviewed retrospectively. Results: In 160 FUS patients, mean follow-up period before referral to our uveitis facilities was 31.6 ± 50.9 months. The most common reason for referral was idiopathic uveitis (61.9%), followed by cataract (25.0%), high intraocular pressure (IOP) including glaucoma (16.3%), and FUS (14.4%). Unilateral involvement was 96.9%. The most frequent ocular finding of FUS was anterior inflammation (91.9%), followed by stellate-shaped keratic precipitates (88.1%), cataract/pseudophakia (88.1%), diffuse iris atrophy (84.4%), vitreous opacity (62.5%), heterochromia (53.1%) and high IOP including glaucoma (36.3%). As treatments of these ocular findings, cataract surgery was performed in 52.5%, glaucoma surgery in 10.6%, and vitrectomy in 13.8%. Mean logMAR VA was 0.28 ± 0.59 at the initial visit, and decreased significantly to 0.04 ± 0.32 at the last visit. Proportions of FUS patients with BCVA < 0.1 and 0.1 to < 0.5 decreased, while that of ≥ 0.5 increased at the last visit compared with the initial visit. Conclusions: Ocular findings of FUS in Japanese FUS patients were consistent with the characteristic features. The low prevalence of FUS in Japan may be a result of being overlooked and misdiagnosed as mild idiopathic uveitis, cataract, and/or glaucoma.